Advances in Evolutionary and Deterministic Methods for Design, Optimization and Control in Engineering and Sciences - Gaspar-Cunha, António; Periaux, Jacques; Giannakoglou, Kyriakos C; Gauger, Nicolas R; Quagliarella, Domenico; Greiner, David (Computational Methods in Applied Sciences, 2020)
This book presents improved and extended versions of selected papers from EUROGEN 2019,  a conference with interest on developing or applying evolutionary and deterministic methods in optimization of design and emphasizing on industrial and societal applications.